Carbon pricing in emerging economies : challenges and opportunities for Türkiye - Ari, Izzet (Routledge, 2025)
Carbon pricing is one of the key policy instruments available to help countries reach the goals of the Paris Agreement and the United Nations Framework Convention on Climate Change (UNFCCC).This book explores the challenges and opportunities facing emerging economies in the implementation of carbon pricing with a particular focus on the case of Trkiye. After introducing the principles and practicalities of carbon pricing mechanisms, the book explores the economic feasibility of Trkiye achieving Nationally Determined Contributions (NDCs) and net zero emissions targets. It is argued that its national circumstances hinder Trkiye's use of carbon crediting mechanisms, auctions for carbon certificate units, and building bilateral and multilateral cooperation with other countries, leaving the voluntary carbon market as the only option. The book explores the implications of this and also highlights the need for improvements and reform in Trkiye's climate laws, public institutions, and international relations to better support carbon pricing. The book also recommends aligning carbon pricing with ongoing energy market reforms, including the replacement of fossil fuel subsidies with more targeted support.This book will be of significant interest to readers of energy economics, environmental economics, emerging economies, and climate change more broadly.
Keywords: Carbon offsetting -- Developing countries.; Carbon offsetting -- Turkey.; Carbon dioxide mitigation -- Economic aspects -- Turkey.; elektronické knihy; electronic books